A close-up of the contemporary view of sexuality in adolescence - De Tilio, R. (2013)
This article presents a study about the speeches of a group of teenagers about sexuality, showing how this subject is apprehended by them. For it to be possible, a group interview was realized in a school. Nine teenagers, with ages between 14 and 17 years old, took part in this. A semistructured interview script was used as the instrument to cover everything about this. It was concluded that there is a shock between the school and the family, about the theme and both were found unprepared. This way, it's necessary to search for strategies that establish the concrete consciousness on the teenagers, as, for example, to create groups in which they can tell their experiences.